The effect of surgical alignment and soft tissue conditions on the kinematics and wear of a fixed bearing total knee replacement. (December 2019) - Johnston, Helena; Abdelgaied, Abdellatif; Pandit, Hemant; Fisher, John; Jennings, Louise M.
Abstract: As life expectancy and activity levels of patients increase so does the demand on total knee replacements (TKRs). Abnormal mechanics and wear of TKRs can lead to implant loosening and revision. Component alignment after surgery varies due to the presurgical alignment, the accuracy of the surgical instrumentation and due to patient factors, such as the soft tissue balance. This study experimentally investigated the effect of variation in component alignment and the soft tissue conditions on the kinematics and wear of a fixed bearing TKR. DePuy Sigma fixed bearing TKRs with moderately cross-linked UHMWPE were used. Different alignment conditions were simulated in the coronal, sagittal and transverse planes in an ISO force-controlled simulation system. Three different soft tissue conditions were simulated using virtual springs to represent a stiff knee, a preserved PCL and a resected PCL. Four different alignment conditions were studied; ideal alignment, 4° tibial and femoral varus joint line, 14° rotational mismatch and 10° posterior tibial slope. The varus joint line alignment resulted in similar kinematics and lower wear rate compared to ideal alignment. The rotational mismatch alignment resulted in significantly higher tibial rotation and abduction-adduction as well as a significantly higher wear rate than ideal alignment. The posterior tibial slope alignment resulted in significantly higher wear than the ideal alignment and dislocated under the lower tension soft tissue conditions. Component alignment and the soft tissue conditions had a significant effect on the kinematics and wear of the TKR investigated in this study. The surgical alignment of the TKR is an important factor in the clinical outcome of the joint as factors such as increased tibial rotation can lead to anterior knee pain and instability and increased wear can lead to aseptic loosening and early failure resulting in revision. Graphical abstract: Image 1 Highlights: Component alignment had a significant effect on the kinematics and wear rates. Varus joint line alignment resulted in similar kinematics and wear to ideal alignment. Rotational mismatch and tibial slope resulted in significantly higher wear rates. "Ideal" soft tissue tensions were different for each alignment condition. The combination of alignment and soft tissue conditions should be investigated.